Strategi, implementasi, dan evaluasi program BSI agen dalam meningkatkan pembiayaan UMKM di bsi KCP Lumajang S. Parman - Aulya, Mimma Alif; Wardana, Guntur Kusuma (Maliki Interdisciplinary Journal, 2025)
This study examines the strategy, implementation, and evaluation of the BSI Agent Program in enhancing MSME financing at BSI KCP Lumajang S. Parman. The BSI Agent Program is an innovation by Bank Syariah Indonesia to expand access to Islamic financial services, particularly in areas far from branch offices. The main strategies include expanding the agent network in strategic locations, improving Islamic financial literacy for MSME actors, and providing financing products tailored to business needs based on Sharia contracts. Implementation is carried out through the recruitment and training of agents, provision of digital devices, and assistance for MSMEs to facilitate access to banking services. Agents act as the bank’s extension, providing transaction services, financing, and financial education. Program evaluation is conducted regularly by monitoring agent performance, customer growth, and repayment performance. The findings indicate that the BSI Agent Program is effective in improving Islamic financial inclusion, expanding MSME access to capital, and contributing to regional economic growth. Beyond its impact on bank profitability, the program also strengthens socio-economic roles by upholding Sharia values such as justice, transparency, and sustainability.